THE EFFECT OF COMPETENCE, TRAINING, AND SUPERVISION OF ASSESOR PERFORMANCE WITH MOTIVATION AS AN INTERVENING VARIABLE AT LEMBAGA SERTIFIKASI PROFESI UNIVERSITAS BHAYANGKARA JAKARTA RAYA - Nugroho Pratomo, Wahyu; Tri Widyastuti; Wastam Wahyu Hidayat (Dinasti International Journal of Digital Business Management, 2022)
This research aims to measure the effect of competence, training and supervision on assessor performance with motivation as an intervening variable at Lembaga Sertifikasi Profesi Universitas Bhayangkara Jakarta Raya. This research is a quantitative study in which the object of the respondent is an assessor registered at Lembaga Sertifikasi Profesi Universitas Bhayangkara Jakarta Raya. The number of samples used as many as 60 respondents. The design used is hypothesis testing using the structural equation model (SEM) – Smart PLS version 3.3.3. The results of this study shows that (1) competence and supervision have a significant effect on motivation, (2) training has no effect on motivation, (3) motivation has a significant effect on assessor performance, (4) competence and supervision through motivation have an effect on assessor performance, (5) training through motivation has no effect on assessor performance.